IMPLEMENTASI PROGRAM KOTA TANPA KUMUH DI KECAMATAN SEMARANG TIMUR - Stevanni Imelda Christianingrum; Titik Djumiarti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
Kota Tanpa Kumuh (KOTAKU) is a programme runned by the Direktorat Jenderal Cipta Karya to support the fulfillment of the RPJMN targets for 2015 - 2019. Presidential Regulation No. 2 of 2015 mandates the construction and development of urban areas through the handling of the residential environments quality. The results of the study shows that East Semarang has 6 urban village that are included in the slum area, namely Bugangan, Rejosari, Mlatiharjo, Mlatibaru, Rejomulyo, Kemijen. KOTAKU programme gets APBN found of 17,2 billion to run the program. Through a qualitative-descriptive approach, this study aims to find out how the implementation of the Kota Tanpa Kumuh (KOTAKU) in the District of East Semarang. There are 5 programmes has to be implemented, namely improvement of building conditions, improvement of environmental roads, provision of drinking water, provision of waste management facilities, and provision of fire protection. The results of the study showed that there was a reduction in the size of the slum area from 415.83 Ha to 118.5 Ha. The implementation of the KOTAKU programme has an inhibiting factor, such as the lack of socialization from the government related to the program in community, and the lack of community participation in the development process. The conclusion of this study is the implementation of KOTAKU in East Semarang has been in accordance with the needs of local community and there was a reduction in the size of slum area 71,5%. This study provides recommendations that, from the government perspective it is necessary to increase socialization related to the program and to coordinate directly with the community to increase participation in the KOTAKU programme. The suggestion for further research is the need for a strategy in socialization carried out bottom-up so that more people are actively involved.